APLIKASI PENGELOLAAN HAMA TERPADU KUMBANG TANDUK (ORYCTES RHINOCEROS L.) PADA KELAPA SAWIT DI NAGARI GIRI MAJU KABUPATEN PASAMAN BARAT - Siska Efendi (LPPM Universitas Andalas, 2021)
Oil palm cultivated in the replanting area did not grow optimally because most were attacked by horn beetles (Oryctes rhinoceros L.). The percentage of horn beetle attacks was high, namely 80% in 3 year old plants and 100% at 1-1.5 years old. It is known that residual replanting waste is the cause of the high horn beetle population because rotting oil palm trunks become a suitable habitat for horn beetle development. To overcome the problems faced by partners, Integrated Pest Management (IPM) is applied. IPM components that will be applied are technical culture, mechanics, and semiochemical control with pheromones. This activity aims to reduce the level of damage to the horn beetle pest on oil palm plants after replanting. This activity is carried out using counseling methods, training, demonstration plots (pilots), providing assistance with tools and machines, as well as monitoring and evaluation. The results of the activity showed that the partners were able to independently implement integrated pest management (IPM) on their respective lands. Assembled IPM technology that has been applied can reduce the attack rate of horn beetles from 86.68% to 79.60%. Until now, IPM equipment is still installed and operated by partner farmer groups. The application of IPM at the demonstration plot locations can significantly reduce the horn beetle population, as well as no more visible symptoms of new plants being attacked. The sustainable application of IPM, covering large-scale land, involving all oil palm business actors will increase the chances of success of the method in the future. will come.